PENERAPAN STRATEGI DIGITAL DALAM PELAYANAN PAJAK DAERAH KOTA BANJARMASIN - Puteri, Aulia; Suharto, Imam; Claudia, Meiske (Universitas Lambung Mangkurat, 2025)
This study aims to describe the implementation of digital strategies in regional tax services at the Regional Revenue and Asset Management Agency (BPKPAD) of Banjarmasin City, as well as to identify challenges and public responses to this transformation. Using a qualitative descriptive approach, data was obtained through interviews, observations, and documentation involving BPKPAD employees and taxpayers as informants. The results indicate that digitalization through the